Successful transcatheter arterial embolization of a ruptured right gastroepiploic artery aneurysm: A case report. (2018) - Ishimine, Tohru; Tengan, Toshiho; Nakasu, Akio; Takara, Hiroaki
Highlights: GEAAs are extremely rare. We describe a case of a ruptured right GEAA treated by TAE. An elderly woman with abdominal pain was diagnosed as having a ruptured right GEAA. The patient was at high risk for surgery so we performed TAE for the ruptured GEAA. The patient had an uneventful recovery and was discharged 10 days after TAE. Abstract: Background: Gastroepiploic artery aneurysms (GEAAs) are extremely rare. Ruptured GEAAs are related to high mortality and often treated by open surgery. We describe a case of a ruptured right GEAA that was successfully treated by transcatheter arterial embolization (TAE). Presentation of case: An 80-year-old woman presented to the emergency department with sudden abdominal pain. We diagnosed her as having a ruptured right GEAA based on the contrast-enhanced computed tomography finding. We performed TAE for the GEAA after resuscitation. The patient had an uneventful recovery and was discharged 10 days after TAE. Discussion: A ruptured GEAA causes high mortality; thus, immediate and adequate treatment is mandatory. Previously, many cases of successful surgical resections of ruptured GEAAs have been reported. In our case, we decided that the patient was not suitable for surgery because of her advanced age and bronchiectasis; therefore, we performed TAE and had a good outcome. Conclusion: In patients at high risk for surgery, TAE can be an effective treatment for a ruptured GEAA.